Earthquake Analysis over the Equatorial Region by Using the Critical Frequency Data and Geomagnetic Index - Nagarajoo, K. (Journal of Engineering and Technology (JET), 2011)
This paper focuses on the variation of the ionosphere in the F2 layer over the equatorial region during seismic event. The critical frequency of the F2 layer, fcF2, shows that there is relationship between the variation of the ionosphere and the occurrence of an earthquake. This fcF2 was obtained from the ground-based ionosonde that has been stationed in Wireless and Radio Science Centre, UTHM. Two statistical techniques, which are the median and mean based techniques, were used to examine the possible relationship between the occurrence of the earthquake with the variations of the fcF2. For this research, two strong earthquakes phenomena occurred in Indonesia were chosen. The results obtained shows that there is strong relationship between the fcF2 and the occurrence of earthquake. Then, fitting method from Matlab was applied to the respective fcF2 data some days before and after the earthquake in order to obtain an analytical equation which can be used as a precursor for the occurrence of an earthquake. However, 2 different earthquakes gave 2 different equations though. Other than ionospheric disturbances, the earthquake also affects the Earth’s magnetic field, which can be measured using geomagnetic index, Kp. However, the Kp does not correlate very well with the variation of the fcF2 during an earthquake.